Roles And Responsibilities Of Port Engineers In Coal Carrying Ship Operations - Rahmat Prasadesta; Aam Bastaman (Jurnal Bisnis dan Manajemen (JURBISMAN), 2026)
The coal logistics sector is highly dependent on the technical readiness of port facilities and the reliability of loading and unloading equipment. This study aims to describe the role and technical responsibilities of Port Engineers, and analyze their contribution to the operational effectiveness of coal carriers, with the research object being Adaro Logistics, South Kalimantan. The research method used is descriptive qualitative supported by quantitative data. Primary data collection was conducted through in-depth interviews, field observations, and questionnaires distributed to various related parties, while secondary data were obtained from port operational documents. The results of the study indicate that Port Engineers have a crucial role as technical managers and liaisons between port operational functions. The implementation of good administrative and coordinative responsibilities by Port Engineers has been proven to stabilize loading levels, reduce equipment downtime, ensure timely ship departures, and reduce the risk of shipping delays. In conclusion, optimizing the role of Port Engineers and the equipment maintenance system has a direct impact on improving operational smoothness and occupational safety in the coal transportation process.